Language learning autonomy among Malaysian ESL tertiary learners: a case study / Asmahanim Mohamad Yusuf - Mohamad Yusuf, Asmahanim (2013)
This study was conducted with the aim to identify the language learning autonomy among Malaysian ESL tertiary learners. The descriptive case study comprised 60 ESL tertiary learners in a college located in a local public university in Selangor, Malaysia. The study employed a mixed-methods research design where data were collected via a questionnaire and semi-structured interviews. The quantitative data was statistically analysed using SPSS version 20 for Mac while the qualitative data was analysed deductively and inductively based on the research questions. The validity and reliability of instruments was established through experts’ opinions and a pilot study. The overall reliability was established at 0.876 alpha levels. The findings revealed that the students were confident in planning and organizing their language learning but were only fairly confident in regards to monitoring and evaluating their language learning. Findings also indicated that there was no significance difference in the mean score between confidence level and gender. Besides that, findings also revealed that the students were reliant on their teachers in language learning but there were no significant difference in the mean score between male and female students’ reliance towards their teachers. Those students perceived their teachers were the expert of the language but they looked forward for more opportunities to give their opinion about classroom materials and activities. Teachers’ reluctance in giving the students opportunities to give their opinion in language classroom, the students’ lack of awareness regarding learner autonomy as well as being too teacher-dependent were some of the main challenges faced by ESL tertiary learners in becoming autonomous learners. The findings imply that learner autonomy should be promoted in ESL classroom by conducting workshops and trainings to both teachers and students. This may serve as the platform to motivate teachers and students in moving towards learner autonomy.